Antarctic tourism and environmental impact assessment - Kriwoken, L (1995)
Arriving by ship and airplane, 8500 tourists visited Antarctica in the 1993-94 season. As tourist numbers grow, the associated environmental impact increases during the short Antarctic summer. Most Antarctic seaborne and airborne tourism companies are members of the International Association of Antarctica Tour Operators (lAATO) and must abide by strict environmental guidelines. Increasingly tourism companies are conducting environmental impact assessments.